A search for warm/hot gas filaments between pairs of SDSS Luminous Red Galaxies. Issue 1 (16th November 2018) - Tanimura, Hideki; Hinshaw, Gary; McCarthy, Ian G; Van Waerbeke, Ludovic; Aghanim, Nabila; Ma, Yin-Zhe; Mead, Alexander; Hojjati, Alireza; Tröster, Tilman
Abstract: We search the Planck data for a thermal Sunyaev–Zel'dovich (tSZ) signal due to gas filaments between pairs of Luminous Red Galaxies (LRGs) taken from the Sloan Digital Sky Survey Data Release 12 (SDSS/DR12). We identify ∼260 000 LRG pairs in the DR12 catalogue that lie within 6–10 h^-1 Mpc of each other in tangential direction and within 6 h^-1 Mpc in radial direction. We stack pairs by rotating and scaling the angular positions of each LRG so they lie on a common reference frame, then we subtract a circularly symmetric halo from each member of the pair to search for a residual signal between the pair members. We find a statistically significant (5.3σ) signal between LRG pairs in the stacked data with a magnitude Δ y = (1.31 ± 0.25) × 10 −8 . The uncertainty is estimated from two Monte Carlo null tests which also establish the reliability of our analysis. Assuming a simple, isothermal, cylindrical filament model of electron overdensity with a radial density profile proportional to r c / r (as determined from simulations), where r is the perpendicular distance from the cylinder axis and r c is the core radius of the density profile, we constrain the product of overdensity and filament temperature to be δ _ c × (T_e/10^7 K) × (r_ c/0.5h^-1 Mpc) = 2.7 ± 0.5 . To our knowledge, this is the first detection of filamentary gas at overdensities typical of cosmological large-scale structure. We compare our result to the BAHAMAS suite of cosmological hydrodynamic simulations (McCarthy et al. 2017 ) and find a slightly lower, but marginally consistent Comptonization excess, Δ y = (0.84 ± 0.24) × 10 −8 .